Prototipo de localización, monitoreo y control vehicular aplicando internet de las cosas, - Parrales Vergara, Rodney Martin (2017)
Nowadays the number of car thefts has increased significantly in the country, thus it is very important to have a proper security installed in the vehicle. The incorporation of elements that guarantee the security of vehicles is scarce, and it is considerably expensive for the owners to contract a private service to lock and track their vehicles. These security elements should allow having a constant tracking of the vehicle state, allowing the owner to carry out any activity during the day without preoccupation that the car will be stolen. Therefore, this project is aimed at general community that, due to everyday tasks o activities, sometimes are obligated to park their vehicles without vigilance. To do this, we propose to develop an economic prototype that contribute favorably to the vehicular security, using current technology; that is, the prototype allows owners the satellite localization in real time and the remote lock of the vehicle by a web application. The proper operation of the prototype was verified using two cars of different brands and models. It is worth mentioning the effectiveness of the prototype depends on the network coverage, but beyond this limitation, our system provides to the owners the tranquility of having information about their vehicles using any mobile device with internet connection.